Aortic endograft infection secondary to Burkholderia pseudomallei: A case report and review of the literature - Sabrina Cheok, MRCSI; Le Si Cherie Gan, MRCP; Shimin Jasmine Chung, MBBS (Hons) (Australia), MRCP (UK); Jack Kian Ch'ng, MB, Bch, BAO (RCS), MMed, FRCS (Ed) (Journal of Vascular Surgery Cases and Innovative Techniques, 2021)
Aortic graft infection is a rare complication after endovascular aneurysm repair that is usually caused by gram-positive organisms such as Staphylococcus spp or gram-negative organisms such as Enterobacteriaceae or Salmonella spp. We have presented a unique case of a patient with acute graft infection secondary to Burkholderia pseudomallei. Because treatment of B. pseudomallei infections is challenging owing to its inherent resistance to multiple antibiotics, we have proposed an approach for managing similar cases in the future. Lifestyle advice on avoiding soil exposure in the postoperative period after endovascular aneurysm repair might be an important preventative measure in endemic regions.